Rattlesnake hemoglobins: Functional properties and tetrameric stability - Lombardi, F. R.; Anazetti, M. C.; Santos, G. C.; Olivieri, JR; de Azevedo, W. F.; Bonilla-Rodriguez, G. O. (Bentham Science Publ Ltd, 2006)
The present work analyzed the tetrameric stability of the hemoglobins from the rattlesnake C. durissus terrificus using analytical gel filtration chromatography, SAXS and osmotic stress. We show that the dissociation mechanism proposed for L. miliaris hemoglobin does not apply for these hemoglobins, which constitute stable tetramers even at low concentrations.
Keywords: hemoglobin; rattlesnake; tetramer stability